Fracionamento de zinco em amostras de leite - Bossu, Carla Maíra (2009)
This work studies were aimed at samples preparation and chemical speciation levels zinc in samples of different kind of milk (milk cattle, sheep, goat, and soybean milk base). The proposal aimed to establish the differences in the zinc levels in protein samples, trying to observe the distribution and zinc bioavailability due to treatments such as pasteurization. The samples were digested in a cavity microwave oven and the total Zn, Ca and P levels in extracts were determined by inductively coupled plasma optical emission spectrometry (ICP OES). An additional study was conducted for protein samples separation in different kinds of milk using the urea polyacrylamide gel electrophoresis (UREA-PAGE) methodology and posterior determination of Zn bound to protein bands. Therefore the protein bands were digested in the cavity microwave oven and the Zn levels were determined by graphite furnace atomic absorption spectrometry (GFAAS). The results displayed that Zn is mainly bound to 32 kDa (β-casein) protein in UHT whole milk and to the 24 kDa (α-casein) protein in raw sheep milk. There were not major differences between the Zn-proteins binding at the pasteurization process. After optimization experimental conditions, in vitro simulated gastric digestion was applied to Zn, Ca and P bioaccessibility in the studied samples. The results confirmed the adopted methodology efficiency. Furthermore, the pasteurization process did not affect the total proteins concentration of bovine milk.